2014
DOI: 10.1002/pd.4376
|View full text |Cite
|
Sign up to set email alerts
|

Does a combination of ultrasound, MRI, and biochemical amniotic fluid analysis improve prenatal diagnosis of esophageal atresia?

Abstract: In case of ultrasound prenatal suspicion of EA (with or without visualization of the pouch sign), an MRI at 30-32 weeks using fast imaging employing steady-state acquisition should be proposed. Biochemical amniotic fluid may be helpful and should be evaluated in a larger study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
1
21
0
3
Order By: Relevance
“…There are few studies evaluating biochemistry of the amniotic fluid in EA . Muller et al showed that digestive enzymes were abnormal in amniotic fluid in case of EA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are few studies evaluating biochemistry of the amniotic fluid in EA . Muller et al showed that digestive enzymes were abnormal in amniotic fluid in case of EA.…”
Section: Discussionmentioning
confidence: 99%
“…They described an EA index with a threshold of 3 allowing 98% of sensibility and 100% of specificity . Using this EA index, Garabadian et al observed 90% of sensibility and 60% of specificity . Because of our study design, we confirm the high sensitivity of amniotic fluid biochemistry (sensitivity 88.2%), but we cannot study the specificity because all cases were EA, and therefore, there were no false‐positive cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations